Effect of mastery learning with two styles variable and stable exercise in learning some skills of attack of basketball - Ali, Dunya (Journal of Physical Education, 2012)
the leerning process interested by many researchers and competent in the education, that is way is very important to use mastery learning in random and skill in basket ball. Problem of research the teacher did not use the modern ways and don’t know defiant of mastery hear ninny most to use give agood chance for learning .